Oxygen-functionalized carbon nanofibers from kulim wood for high- performance supercapacitors via an integrated chemical–physical catalyst approach - Taer, Erman; Apriwandi; Tambunan, Ebigail Nur Tabita; Yanti, Novi; Nursyafni; Taslim, Rika (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
This study highlights the critical role of oxygen-functionalized hierarchical nanofiber structures derived from kulim wood waste in improving the electrochemical performance of symmetric supercapacitors. A one-step catalyst-assisted method was developed to synthesize these carbon nanofibers. The synthesized material exhibited well-defined oxygen functionalities (9.34% oxygen content) and exceptional porosity (1070 m2/g), demonstrating a micro-mesoporosity ratio of nearly 4:1. This structural design led to enhanced capacitive properties, achieving a capacity of 172 F/g in acid media and a rate capability of 81.2% at 10 A/g. The oxidation reactions indicated a mixed energy storage mechanism, with 83% EDL-controlled and 22% redox-controlled processes. Additionally, the material showed an energy output of 19.91 Wh/kg and a power density of 1.02 kW/kg, showcasing its potential for sustainable energy storage applications. Importantly, this work offers a scalable, low-cost, and biomass-driven strategy for producing high-performance carbon electrodes, advancing sustainable supercapacitor technologies.